The Maastricht Treaty and the ECJ in the Light of its Recent Case Law - Csehi, Zoltán (Maastricht 30: A Central European Perspective, 2025)
The Maastricht Treaty introduced the Court of First Instance into primary law of the Union as a first instance court in certain matters. This paper discusses the evolution of the system of appeals against the decisions of that court before the ECJ. The development of the case law of the ECJ concerning the sanctioning of Member States for non-compliance with the judgments of the ECJ, which was introduced by the Maastricht Treaty, shows some particularity, as addressed in the second chapter of the paper. EU citizenship is the third topic elaborated on in the paper in connection with the loss of the nationality of a Member State and Brexit. The CFSP, which is also a novelty of the Maastricht Treaty, proves to be a field of ongoing ECJ competence issues, as attested by the recent case law of that court. Keywords: Maastricht, Court of Justice of the European Union, General Court, sanction mechanism, lump sum or penalty payment, EU citizenship, CFSP